Breakthrough! : how the 10 greatest discoveries in medicine saved millions and changed our view of the world - Queijo, Jon , 1955- (FT Press Science, 2010)
In this book, the author tells the hidden stories history's most amazing medical discoveries. This isn't dry history: these are life and death mysteries uncovered, tales of passionate, often mocked individuals who stood their ground and were proven right; they include a colorful cast of characters whose discoveries were often driven not only by personal tragedy, curiosity, and hard work, but petty bickering, dumb luck, and a healthy dose of humor. From germs to genetics, the ancient Hippocrates to the cutting edge, these are events that have changed the world, and saved lives. He discusses ten world changing revolutions in medicine and the human discoveries that made them possible, the stories behind antibiotics, vaccines, DNA, X-rays, and more. He relates what happened, how it happened, and what it means today. Revolutionary medical breakthroughs like these haven't just changed the way we treat disease, they have transformed how we understand ourselves and the world we live in